AST TO PLATELET RATIO INDEX (APRI) AND DEGREE OF SEVERITY BASED ON CHILD-PUGH CLASSIFICATION AMONG CIRRHOSIS PATIENTS AT INTERNAL MEDICINE WARD IN A TERTIARY HOSPITAL - Winanda Denis Kurniawan; Budi Widodo; Betty Agustina (Majalah Biomorfologi, 2022)
Highlights: 1. The Child-Pugh score is an instrument to assess the degree of severity and prognosis of chronic liver disease. 2. the rise in APRI score may predict the advance of cirrhosis stages. Abstract: Background: Simple diagnostic and screening methods are needed to assist with liver biopsy, which is not always available in local health facilities. Objective: To assess the AST-to-Platelet Count Index (APRI) as a means to predict the advance of cirrhosis stages as indicated in Child-Pugh classification. Material and Method: This research employed an observational descriptive study design to examine laboratory values such as serum AST and platelet count, which were then compared to Child-Pugh profiles among cirrhosis patients at an inpatient facility in a tertiary hospital of Dr Soetomo General Academic Hospital, Surabaya, Indonesia on 1 January – 31 December 2015. The sampling method for this research was total sampling from medical histories. Result: Data obtained were then analyzed and tabulated using the descriptive technique. As many as 191 samples were obtained, consisting of male (N=129, 67.54%) and female patients (N=62, 32.46%) with a ratio of 2.08:1. APRI score showed an increase in age, with a peak frequency of 68 patients (35.6%) in the range 50-59 years old. Male patients had a higher average APRI score (2.11) than their female counterparts (1.93). Patients from Child C were the majority in this research, consisting of 105 patients (54.9%), followed by Child B (N=65, 34.03%) and A (N=21, 10.9%). Conclusion: The proportion of patients with APRI score > 1.5 is increasing along with the degree of severity according to the Child-Pugh classification. This indicates that the rise in APRI score may predict the advance of cirrhosis stages.